THE IMPLEMENTATION OF PUBLIC HEALTH SERVICES FOR BPJS PATIENTS AND GENERAL PATIENTS AT WALUYO JATI REGIONAL PUBLIC HOSPITAL - Siti Baitir Rohimah; Rini Rahayu Kurniati; Khoiron (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Health services constitute a fundamental element in the administration of public governance, particularly as they relate to citizens’ basic rights to access quality and equitable health protection. This study examines in depth the dynamics of responsiveness and accountability in public service delivery within the context of healthcare services at RSUD Waluyo Jati Kraksaan, focusing on two primary groups of service users: BPJS patients and general patients. The analysis is conducted through the theoretical framework of New Public Service (NPS), which positions the public interest as the central objective of service delivery and emphasizes that government and public institutions must serve citizens in a humane, empathetic, participatory, and democratic manner. The research employs a descriptive qualitative approach to understand service-related phenomena within their social context, relying on in-depth interviews, field observations, and administrative documentation. The findings indicate that RSUD Waluyo Jati demonstrates an initial commitment to providing equitable and public-oriented services; however, in practice, several complex gaps remain. These include prolonged waiting times for BPJS patients, disparities in service perceptions between BPJS and general patients, limited communication between the hospital and service users, and suboptimal transparency in service procedures. The implementation of key NPS principles such as Serve Rather Than Steer, The Public Interest Is the Aim, and Accountability and Transparency has not yet been fully realized in daily service practices. This study concludes that strengthening service digitalization, enhancing public communication capacity, reforming queue management systems, and simplifying BPJS administrative procedures constitute strategic measures to improve the delivery of responsive and accountable healthcare services.